2016
DOI: 10.1038/nature19790
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of Ebola virus: Insights from the 2013–2016 epidemic

Abstract: Preface The 2013–2016 epidemic of Ebola virus disease in West Africa was of unprecedented magnitude and changed our perspective on this lethal but sporadically emerging virus. This outbreak also marked the beginning of large-scale real-time molecular epidemiology. Herein, we show how evolutionary analyses of Ebola virus genome sequences provided key insights into virus origins, evolution, and spread during the epidemic. We provide basic scientists, epidemiologists, medical practitioners, and other outbreak res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
236
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 277 publications
(259 citation statements)
references
References 94 publications
14
236
0
4
Order By: Relevance
“…From a disease prevention point of view, screening and detection of Human papillomavirus infection provides protection against the development of invasive cervical cancer (Ronco et al, 2014), detection of Heliocobacter pylori is indicative of risk for peptic ulcers (Chan et al, 2002), and hospital outbreak as well as epidemic investigations via pathogen sequencing can identify the initial source of an infection and prevent its transmission (Holmes et al, 2016; Lefterova et al, 2015). Pathogen sequencing is also being increasingly utilized in environmental monitoring applications, for example by monitoring influenza reservoirs in animal populations, identifying novel viral antigens, and ultimately informing the development of seasonal vaccines (Ampofo et al, 2015).…”
Section: High Definition Preventionmentioning
confidence: 99%
“…From a disease prevention point of view, screening and detection of Human papillomavirus infection provides protection against the development of invasive cervical cancer (Ronco et al, 2014), detection of Heliocobacter pylori is indicative of risk for peptic ulcers (Chan et al, 2002), and hospital outbreak as well as epidemic investigations via pathogen sequencing can identify the initial source of an infection and prevent its transmission (Holmes et al, 2016; Lefterova et al, 2015). Pathogen sequencing is also being increasingly utilized in environmental monitoring applications, for example by monitoring influenza reservoirs in animal populations, identifying novel viral antigens, and ultimately informing the development of seasonal vaccines (Ampofo et al, 2015).…”
Section: High Definition Preventionmentioning
confidence: 99%
“…It has been suggested that recent ZIKV epidemics may be linked causally to a higher apparent evolutionary rate for the Asian genotype than the African genotype 25,26 . However, such comparisons are confounded by an inverse relationship between the timescale of observation and estimated evolutionary rates 27 .…”
mentioning
confidence: 99%
“…Moreover, the approaches that are farthest advanced in the pipeline exclusively target the Zaire ebolavirus. Despite this focus, EBOV accounted for only 58% of EVD cases prior to the 2014 outbreak (20). Thus, the benefit of broader therapeutic approaches is clear.…”
Section: Discussionmentioning
confidence: 99%